THE INFLUENCE OF ADDITIONAL EMPLOYEE INCOME ON EMPLOYEE PERFORMANCE IN THE LAND OFFICE EAST LAMPUNG DISTRICT - Fauzi, Fauzi; Aliyah, Hikmatul; Saputro, Joko (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Conceptually and empirically, measurement of staff performance and additional income is closely linked to the core tasks and functions of the work unit. Additional amount of income for civil servants is awarded based on the respective posts occupied by officials, both structural and functional. The research is aimed at finding out the impact of the employee income tax on the performance of employee farm office in East Lampung district. This research uses descriptive quantitative methods. The data collection technique in this study is a questionnaire with samples of 46 respondents using saturated sampling techniques. The data analysis technique used in this study is simple regression with the help of the SPSS 16 application. Conceptually and empirically, measurement of staff performance and additional income is closely linked to the core tasks and functions of the work unit. Additional Scale The results of this study suggest that the additional variable of employee income has a positive and significant impact on the performance of the employee of the land office of the East Lampung District. As for the correlation coefficient of 51.2%, while the remaining 48.8% was influenced by other factors that were not included in this study. Keywords: additional employee income, performance